RETRACTED: Acceleration and deceleration control algorithm of CNC system based on deep neural network reinforcement learning and MCU - Zheng, Guangyuan; Cheng, Chen; Dong, Xinling; Liu, Yi (Journal of intelligent & fuzzy systems, 2024)
This article has been retracted. A retraction notice can be found at https://doi.org/10.3233/JIFS-219433.